Věra Thořová, Jiří Traxler, Zdeněk Vejvoda: LIDOVÉ PÍSNĚ Z PRAHY ve sbírce Františka Homolky. I. díl [Folk Songs from Prague in the Collection of František Homolka, 1st Volume.]: Prague: Institute of Ethnology of the Academy of Sciences of the Czech Republic, 2011, 508 pp. Studies, critical edition, photographs, appendices. - Jurková, Zuzana (Lidé města, 2012)
A review of the book by Věra Thořová, Jiří Traxler and Zdeněk Vejvoda.